Food webs and the dynamics of marine reefs - McClanahan, T. R.; Branch, George (Oxford Oxford University Press, 2008)
'Food Webs and the Dynamics of Marine Reefs' summarizes recent developments in the ecology of kelp forests and coral reefs in order to develop an understanding of the general principles of their ecological organization and how they might be managed from an ecosystem perspective.
Electronic reproduction.
Keywords: Food chains (Ecology); Coral reef ecology; Electronic books